2000
DOI: 10.1126/science.288.5474.2219
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Guanosine Triphosphatase Rac2 in T Helper 1 Cell Differentiation

Abstract: T helper 1 (TH1) cells mediate cellular immunity, whereas TH2 cells potentiate antiparasite and humoral immunity. We used a complementary DNA subtraction method, representational display analysis, to show that the small guanosine triphosphatase Rac2 is expressed selectively in murine TH1 cells. Rac induces the interferon-gamma (IFN-gamma) promoter through cooperative activation of the nuclear factor kappa B and p38 mitogen-activated protein kinase pathways. Tetracycline-regulated transgenic mice expressing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 22 publications
9
129
1
Order By: Relevance
“…At the current time it is unknown whether the predominant effect of Rac2 deficiency on the respiratory burst reflects its function in the NADPH oxidase complex itself or in the preceding steps leading to enzyme assembly. However, since multiple functional abnormalities in other BMderived cells have been identified in rac2 Ϫ/Ϫ mice (11,29,30), we speculate that defects in intracellular signaling pathways account for at least some of the observed decrease in superoxide production in response to specific agonists. Why Rac1 is unable to substitute for Rac2 in superoxide production, chemotaxis, and other functional responses that are impaired in Rac2-deficient blood cells also remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the current time it is unknown whether the predominant effect of Rac2 deficiency on the respiratory burst reflects its function in the NADPH oxidase complex itself or in the preceding steps leading to enzyme assembly. However, since multiple functional abnormalities in other BMderived cells have been identified in rac2 Ϫ/Ϫ mice (11,29,30), we speculate that defects in intracellular signaling pathways account for at least some of the observed decrease in superoxide production in response to specific agonists. Why Rac1 is unable to substitute for Rac2 in superoxide production, chemotaxis, and other functional responses that are impaired in Rac2-deficient blood cells also remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deficiency of Rac2, a hematopoietic-specific Rho GTPase, is associated with a variety of functional defects in murine BMderived cells due to abnormalities in intracellular signaling pathways (11,29,30) despite the presence of the highly homologous Rac1 (Fig. 1) and, probably, Rac3 (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the importance of NF‐κB signaling in the pathogenesis of JIA, as has been established in RA 32. NF‐κB is a major inflammatory regulator and has a role in activation and proliferation of RA FLS and the development of the Th1 helper subset 32, 33, 34. TNF has been shown to induce a TNFR2/NF‐κB‐dependent proinflammatory program in Tregs derived from JIA synovial fluid 35, but ours is the first work to show the activity of NF‐κB signaling in JIA FLS.…”
Section: Resultsmentioning
confidence: 73%
“…It is reasonable to hypothesize that increased Rac2 expression is one of the factors involved in corneal graft failure as Rac2 had been demonstrated to play a central role in T helper 1 (Th1), cell differentiation, and cytokine production. 17 Evidence from studies in mouse and rat models have shown the predominance of Th1 cytokine expression in cells infiltrating the graft during corneal allograft rejection. [18][19][20] The Th1 cytokine, interferon-g, as well as other cytokines, such as IL-1b, IL-2, IL-12, have also been shown to compromise ocular immune privilege, and their upregulation may contribute to graft rejection.…”
Section: Discussionmentioning
confidence: 99%